Delivering safer conception services to HIV serodiscordant couples in Kenya: perspectives from healthcare providers and HIV serodiscordant couples. (20th February 2017) - Ngure, Kenneth; Kimemia, Grace; Dew, Kristin; Njuguna, Njambi; Mugo, Nelly; Celum, Connie; Baeten, Jared M; Heffron, Renee
Abstract: Introduction : For HIV serodiscordant couples in resource‐limited settings, pregnancy is common despite the risk of sexual and/or perinatal HIV transmission. Some safer conception strategies to reduce HIV transmission during pregnancy attempts are available but often not used for reasons including knowledge, accessibility, preference and others. We sought to understand Kenyan health providers' and HIV serodiscordant couples' perspectives and experiences with safer conception. Methods : Between August 2015 and March 2016, we conducted key informant interviews (KIIs) with health providers from public and private HIV care and fertility clinics and in‐depth interviews (IDIs) and focus group discussions (FGDs) with HIV serodiscordant couples participating in an open‐label study of integrated pre‐exposure prophylaxis (PrEP) and antiretroviral therapy (ART) for HIV prevention (the Partners Demonstration Project). An inductive analytic approach identified a number of themes related to experiences with and perceptions of safer conception strategies. Results : We conducted 20 KIIs with health providers, and 21 IDIs and 4 FGDs with HIV serodiscordant couples. HIV clinic providers frequently discussed timed condomless sex and antiretroviral medications while providers at private fertility care centres were more comfortable recommending medically assisted reproduction. Couples experienced with ART and PrEP reported that they were comfortable using these strategies to reduce HIV risk when attempting pregnancy. Timed condomless sex in conjunction with ART and PrEP was a preferred strategy, often owing to them being available for free in public and research clinics, as well as most widely known; however, couples often held inaccurate knowledge of how to identify days with peak fertility in the upcoming menstrual cycle. Conclusions : Antiretroviral‐based HIV prevention is acceptable and accessible to meet the growing demand for safer conception services in Kenya, since medically assisted interventions are currently cost prohibitive. Cross‐disciplinary training for health providers would expand confidence in all prevention options and foster the tailoring of counselling to couples' preferences.